Synthesis of dibenzosuberenone-based novel polycyclic π-conjugated dihydropyridazines, pyridazines and pyrroles - Koçak, Ramazan; Daştan, Arif (Beilstein Journal of Organic Chemistry, 2021)
The synthesis of novel polycyclic π-conjugated dihydropyridazines, pyridazines, and pyrroles was studied. Dihydropyridazine dyes were synthesized by inverse electron-demand Diels–Alder cycloaddition reactions between a dibenzosuberenone and tetrazines that bear various substituents. The pyridazines were synthesized in high yields by oxidation of dihydropyridazine-appended dibenzosuberenones with PIFA or NO. p-Quinone derivatives of pyridazines were also obtained by H-shift isomerization following the inverse electron-demand Diels–Alder reaction of tetrazines with p-quinone dibenzosuberenone. Then these pyridazines were converted to the corresponding pyrroles by reductive treatment with zinc. It was observed that all the dihydropyridazines obtained gave absorbance and emission at long wavelengths.
Keywords: dibenzosuberenone; inverse electron-demand Diels–Alder cycloaddition reactions; p-quinone methide; polycyclic π-conjugated dihydropyridazines; pyridazines; pyrroles

(untitled) - Koeberle, S. C.; Fischer, S.; Schollmeyer, D.; Schattel, V.; Grütter, C.; Rauh, D.; Laufer, S. A. (J. Med. Chem., 2012)

(untitled) - Murray, M. A.; Babe, L. M. (Antiviral Res., 1999)

(untitled) - Silver, H.; Blacker, M.; Weller, M. P. I.; Lerer, B. (Biol. Psychiatry, 1989)

(untitled) - Andersen, J. M.; Sugerman, K. S.; Lockhart, J. R.; Weinberg, W. A. (Pediatrics, 1997)

(untitled) - Wilens, T. E.; Biederman, J.; Geist, D. E.; Steingard, R.; Spencer, T. (J. Am. Acad. Child Adolesc. Psychiatry, 1993)

(untitled) - Prince, J. B.; Wilens, T. E.; Biederman, J.; Spencer, T. J.; Millstein, R.; Polisner, D. A.; Bostic, J. Q. (J. Child Adolesc. Psychopharmacol., 2000)

(untitled) - Thompson, C. (Br. J. Psychiatry, 2001)

Antidepressants, antipsychotics, anxiolytics from chemistry and pharmacology to clinical application - Buschmann, H.; Díaz, J. L.; Holenz, J.; Párraga, A.; Torrens, A.; Vela, J. M. (Wiley-VCH, 2007)

Pharmaceutical manufacturing encyclopedia - Sittig, M. (Noyes Publications, 1988)

Handbook of affective disorders - Paykel, E. S. (The Guilford Press, 1992)

(untitled) - Vaugeois, J.-M.; Corera, A. T.; Deslandes, A.; Costentin, J. (Pharmacol., Biochem. Behav., 1999)

(untitled) - Chou, R.; Peterson, K.; Helfand, M. (J. Pain Symptom Manage., 2004)

(untitled) - Bume, D. D.; Pitts, C. R.; Jokhai, R. T.; Lectka, T. (Tetrahedron, 2016)

(untitled) - Wang, Z.; Shao, H.; Ye, J.; Tang, L.; Lu, P. (J. Phys. Chem. B, 2005)

(untitled) - Shao, H.; Chen, X.; Wang, Z.; Lu, P. (J. Phys. Chem. B, 2007)

(untitled) - Brosius, V.; Müller, M.; Borstelmann, J.; Rominger, F.; Freudenberg, J.; Bunz, U. H. F. (J. Org. Chem., 2020)

(untitled) - Hirai, M.; Tanaka, N.; Sakai, M.; Yamaguchi, S. (Chem. Rev., 2019)

(untitled) - Shankar, M.; Ghosh, K.; Mukherjee, K.; Rit, R. K.; Sahoo, A. K. (Org. Lett., 2016)

(untitled) - Stępień, M.; Gońka, E.; Żyła, M.; Sprutta, N. (Chem. Rev., 2017)

(untitled) - Huang, R.; Phan, H.; Herng, T. S.; Hu, P.; Zeng, W.; Dong, S.-q.; Das, S.; Shen, Y.; Ding, J.; Casanova, D.; Wu, J. (J. Am. Chem. Soc., 2016)

(untitled) - Kethe, A.; Li, A.; Klumpp, D. A. (Tetrahedron, 2012)

(untitled) - Zheng, X.; Su, R.; Wang, Z.; Wang, T.; Bin, Z.; She, Z.; Gao, G.; You, J. (Org. Lett., 2019)

(untitled) - Bockholt, H.; Beale, J. M.; Rohr, J. (Angew. Chem., Int. Ed. Engl., 1994)

(untitled) - Gerwick, B. C.; Fields, S. S.; Graupner, P. R.; Gray, J. A.; Chapin, E. L.; Cleveland, J. A.; Heim, D. R. (Weed Sci., 1997)

(untitled) - Wermuth, C. G. (Med. Chem. Commun., 2011)

(untitled) - Worms, P.; Kan, J.-P.; Steinberg, R.; Terranova, J.-P.; Perio, A.; Biziere, K. (Naunyn-Schmiedeberg's Arch. Pharmacol., 1989)

(untitled) - Biziere, K.; Worms, P.; Kan, J.; Mandel, P.; Garattini, S.; Roncucci, R. (Drugs Exp. Clin. Res., 1985)

(untitled) - McTavish, D.; Young, R. A.; Clissold, S. P. (Drugs, 1990)

(untitled) - Iizawa, Y.; Okonogi, K.; Hayashi, R.; Iwahi, T.; Yamazaki, T.; Imada, A. (Antimicrob. Agents Chemother., 1993)

(untitled) - Aleeva, G. N.; Molodavkin, G. M.; Voronina, T. A. (Bull. Exp. Biol. Med., 2009)

(untitled) - Rezaei, Z.; Sharbaf, F. R.; Pourmojieb, M.; Youefzadeh-Fard, Y.; Motevalian, M.; Khazaeipour, Z.; Esmaeili, S. (Acta Med. Iran., 2011)

(untitled) - Bansal, R.; Kumar, D.; Carron, R.; de la Calle, C. (Eur. J. Med. Chem., 2009)

(untitled) - Islam, M.; Siddiqui, A. A.; Rajesh, R. (Acta Pol. Pharm., 2008)

(untitled) - Banerjee, P.; Sharma, P.; Nema, R. (Int. J. ChemTech Res., 2009)

(untitled) - Rathish, I. G.; Javed, K.; Bano, S.; Ahmad, S.; Alam, M. S.; Pillai, K. K. (Eur. J. Med. Chem., 2009)

(untitled) - Rathish, I. G.; Javed, K.; Ahmad, S.; Bano, S.; Alam, M. S.; Akhter, M.; Pillai, K. K.; Ovais, S.; Samim, M. (Eur. J. Med. Chem., 2012)

(untitled) - Siddiqui, A. A.; Mishra, R.; Shaharyar, M.; Husain, A.; Rashid, M.; Pal, P. (Bioorg. Med. Chem. Lett., 2011)

(untitled) - Al-Harbi, N. O.; Bahashwan, S. A.; Shadid, K. A. (J. Am. Sci., 2010)

(untitled) - Do, J.; Kim, Y.; Attias, A.-J.; Kreher, D.; Kim, E. (J. Nanosci. Nanotechnol., 2010)

(untitled) - Lincker, F.; Kreher, D.; Attias, A.-J.; Do, J.; Kim, E.; Hapiot, P.; Lemaître, N.; Geffroy, B.; Ulrich, G.; Ziessel, R. (Inorg. Chem., 2010)

(untitled) - Atılgan, N.; Algı, F.; Önal, A. M.; Cihaner, A. (Tetrahedron, 2009)

(untitled) - Asil, D.; Cihaner, A.; Önal, A. M. (Electrochim. Acta, 2009)

(untitled) - Yu, Q.; Zhang, A.-S.; Hu, T.-L.; Bu, X.-H. (Solid State Sci., 2010)

(untitled) - Panigati, M.; Donghi, D.; D'Alfonso, G.; Mercandelli, P.; Sironi, A.; D'Alfonso, L. (Inorg. Chem., 2006)

(untitled) - Donghi, D.; D’Alfonso, G.; Mauro, M.; Panigati, M.; Mercandelli, P.; Sironi, A.; Mussini, P.; D’Alfonso, L. (Inorg. Chem., 2008)

(untitled) - Beckmann, U.; Brooker, S. (Coord. Chem. Rev., 2003)

(untitled) - Park, Y. S.; Kim, D.; Lee, H.; Moon, B. (Org. Lett., 2006)

(untitled) - Cuccia, L. A.; Lehn, J.-M.; Homo, J.-C.; Schmutz, M. (Angew. Chem., Int. Ed., 2000)

Heterocyclic chemistry - Joule, J. A.; Mills, K. (John Wiley & Sons, 2008)

(untitled) - Saracoglu, N. (Tetrahedron, 2007)

(untitled) - Schoch, J.; Wiessler, M.; Jäschke, A. (J. Am. Chem. Soc., 2010)

(untitled) - Devaraj, N. K.; Upadhyay, R.; Haun, J. B.; Hilderbrand, S. A.; Weissleder, R. (Angew. Chem., Int. Ed., 2009)

(untitled) - Kocak, R.; Akın, E. T.; Kalın, P.; Talaz, O.; Saracoglu, N.; Dastan, A.; Gülcin, I.; Durdagi, S. (J. Heterocycl. Chem., 2016)

(untitled) - Kocak, R.; Dastan, A.; Saracoglu, N. (J. Heterocycl. Chem., 2018)

(untitled) - Koçak, R.; Yıldız, D.; Bozkaya, U.; Daştan, A.; Bozdemir, Ö. A. (Tetrahedron Lett., 2017)

(untitled) - Erdoğan, M.; Daştan, A. (Tetrahedron, 2020)

(untitled) - Robins, L. I.; Carpenter, R. D.; Fettinger, J. C.; Haddadin, M. J.; Tinti, D. S.; Kurth, M. J. (J. Org. Chem., 2006)

(untitled) - Farha, O. K.; Malliakas, C. D.; Kanatzidis, M. G.; Hupp, J. T. (J. Am. Chem. Soc., 2010)

(untitled) - Li, Y.; Asadi, A.; Perrin, D. M. (J. Fluorine Chem., 2009)

(untitled) - Vo, H.-L.; Arthur, J. L.; Capdevila-Cortada, M.; Lapidus, S. H.; Stephens, P. W.; Novoa, J. J.; Arif, A. M.; Nagi, R. K.; Bartl, M. H.; Miller, J. S. (J. Org. Chem., 2014)

(untitled) - Ishmetova, R. I.; Latosh, N. I.; Ganebnykh, I. N.; Ignatenko, N. K.; Tolshchina, S. G.; Rusinov, G. L. (Russ. J. Org. Chem., 2009)

(untitled) - Glidewell, C.; Lightfoot, P.; Royles, B. J. L.; Smith, D. M. (J. Chem. Soc., Perkin Trans. 2, 1997)

(untitled) - Abdo, M.; Brown, S. P.; Courter, J. R.; Tucker, M. J.; Hochstrasser, R. M.; Smith, A. B., III (Org. Lett., 2012)

(untitled) - Benson, S. C.; Palabrica, C. A.; Snyder, J. K. (J. Org. Chem., 1987)

(untitled) - Degtyarenko, A. S.; Solntsev, P. V.; Krautscheid, H.; Rusanov, E. B.; Chernega, A. N.; Domasevitch, K. V. (New J. Chem., 2008)

(untitled) - Bach, N. J.; Kornfeld, E. C.; Jones, N. D.; Chaney, M. O.; Dorman, D. E.; Paschal, J. W.; Clemens, J. A.; Smalstig, E. B. (J. Med. Chem., 1980)

(untitled) - Boger, D. L.; Coleman, R. S.; Panek, J. S.; Yohannes, D. (J. Org. Chem., 1984)

(untitled) - Boger, D. L.; Patel, M. (J. Org. Chem., 1988)

(untitled) - Taljaard, B.; Taljaard, J. H.; Imrie, C.; Caira, M. R. (Eur. J. Org. Chem., 2005)